The Swiss Alpine zero degree line: Methods, past evolution and sensitivities. (16th June 2021) - Scherrer, Simon C.; Gubler, Stefanie; Wehrli, Kathrin; Fischer, Andreas M.; Kotlarski, Sven
Abstract: The near‐surface zero degree line (ZDL) is a key isotherm in mountain regions worldwide, but a detailed analysis of methods for the ZDL determination, their properties and applicability in a changing climate is missing. We here test different approaches to determine the near‐surface ZDL on a monthly scale in the Swiss Alps. A non‐linear profile yields more robust and more realistic ZDLs than a linear profile throughout the year and especially in the winter‐half year when frequent inversions disqualify a linear assumption. In the period 1871–2019, the Swiss ZDL has risen significantly in every calendar month: In northern Switzerland, the monthly ZDL increases generally amount to 300–400 m with smaller values in April and September (200–250 m) and a larger value in October (almost 500 m). The largest increases of 600–700 m but also very large uncertainties (±400 m, 95% confidence interval) are found in December and January. The increases have accelerated in the last decades, especially in spring and summer. The ZDL is currently increasing by about 160 m·°C −1 warming in the summer‐half year and by up to 340 ± 45 m·°C −1 warming in winter months. In southern Switzerland, ZDL trends and temperature scalings are somewhat smaller, especially in winter. Sensitivity analyses using a simple shift of the non‐linear temperature profile suggest that the winter ZDL‐temperature scalings are at a record high today or will reach it in the near future, and are expected to decrease with a strong future warming. Nevertheless, the cumulative ZDL increase for strong warming is considerably larger in winter than in summer. Based on a few key criteria, we also present best practises to determine the ZDL in mountain regions worldwide. The outlined methods lay a foundation for the analysis of further isotherms and to study the future ZDL evolution based on climate scenario data. Abstract : We present an assessment of methods to determine the near‐surface zero degree line (ZDL) for the testbed of the Swiss Alps. An approach using a non‐linear profile works best and we find a significantly increasing ZDL and accelerating trends in the last decades. The Alpine winter ZDL‐temperature scaling shows a maximum today and is expected to decrease with a strong future warming. We also provide best practises to determine the ZDL in mountain regions worldwide.